Legal Review Of Shareholder Protection In The Online Application Related To The Dissolution Of The Issuer - Handayani, Ninik (Dinasti Research, 2024)
One of the alternative ways that people can use to invest is the use of online investment applications which are now widespread and easy for people to use. As a place to invest, a securities application is needed to make it easier for people to invest in the capital market. However, it cannot be denied that a company listed on the stock exchange experiences delisting for some reason. This could happen because the company goes bankrupt or other things. So it is necessary to review shareholder protection in online applications if there are problems that require the issuer to be dissolved and delisted from the stock exchange. This research uses a qualitative method with a type of normative juridical research which uses secondary legal sources originating from primary legal materials from statutory regulations and secondary legal materials originating from books, journals and other literature. The research results show that shareholder protection in online applications regarding the dissolution of issuers, custodian banks play an important role in maintaining the flow of transactions in the capital market. Based on Article 46 of Law no. Article 8 of 1995 concerning Custodian Banks in the Capital Market is responsible for all losses resulting from their actions and their form and value in more detail, so that if losses arise they can be immediately borne by the bank.